Some Peculiarities in the Dose Dependence of Separate and Combined In Vitro Cardiotoxicity Effects Induced by CdS and PbS Nanoparticles With Special Attention to Hormesis Manifestations - Vladimir Panov; Ilzira Minigalieva; Tatiana Bushueva; Eleonore Fröhlich; Claudia Meindl; Markus Absenger-Novak; Vladimir Shur; Ekaterina Shishkina; Vladimir Gurvich; Larisa Privalova; Boris A. Katsnelson (SAGE Publishing, 2020)
Spherical nanoparticles (NPs) of cadmium and lead sulfides (diameter 37 ± 5 and 24 ± 4 nm, respectively) have been found to be cytotoxic for HL-1 cardiomyocytes as evidenced by decrease in adenosine triphosphate-dependent luminescence. Cadmium sulfide (CdS)-NPs were discovered to produce a much greater cytotoxic impact than lead sulphide (PbS)-NP. Given the same dose range, CdS-NP reduced the number of calcium spikes. A similar effect was observed for small doses of PbS-NP. In addition to cell hypertrophy under the impact of certain doses of CdS-NP and PbS-NP, doses causing cardiomyocyte size reduction were identified. For these 3 outcomes, we obtained both monotonic "dose-response" functions (well approximated by the hyperbolic function) and different variants of non-monotonic ones for which we found adequate mathematical expressions by modifying certain models of hormesis available in the literature. Data analysis using a response surface linear model with a cross-term provided new support to the previously established postulate that a diversity of types of joint action characteristic of one and the same pair of damaging agents is one of the important assertions of the general theory of combined toxicity.